2023
DOI: 10.3389/frai.2023.1171256
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithms for predicting determinants of COVID-19 mortality in South Africa

Emmanuel Chimbunde,
Lovemore N. Sigwadhi,
Jacques L. Tamuzi
et al.

Abstract: BackgroundCOVID-19 has strained healthcare resources, necessitating efficient prognostication to triage patients effectively. This study quantified COVID-19 risk factors and predicted COVID-19 intensive care unit (ICU) mortality in South Africa based on machine learning algorithms.MethodsData for this study were obtained from 392 COVID-19 ICU patients enrolled between 26 March 2020 and 10 February 2021. We used an artificial neural network (ANN) and random forest (RF) to predict mortality among ICU patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…This highlights that the choice of variables can significantly impact the variables identified as associated with the outcome. Moreover, their model exhibited different performance metrics compared to ours, achieving a recall of 76% and a precision of 87%, whereas our model achieved a higher recall of 90.1% and precision of 84.9%, indicating that our model correctly identified more true positives ( Chimbunde et al, 2023 ; Hicks et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This highlights that the choice of variables can significantly impact the variables identified as associated with the outcome. Moreover, their model exhibited different performance metrics compared to ours, achieving a recall of 76% and a precision of 87%, whereas our model achieved a higher recall of 90.1% and precision of 84.9%, indicating that our model correctly identified more true positives ( Chimbunde et al, 2023 ; Hicks et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 61%
“… Chimbunde et al (2023) utilized RF to predict determinants of COVID-19 mortality in South Africa. Surprisingly, their analysis revealed that being female was associated with increased mortality, contrary to findings from our study and others, which suggested that being female was protective ( Elhazmi et al, 2022 ; Kar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Review of Related Works The computational learning approach has been proven to be a reliable tool in predicting various maternal outcomes, such as full-term delivery (Predicting induced labour outcomes for full-term pregnancies using an Intuitionistic Fuzzy Approach for maternal outcome prediction [12], [13]), miscarriage (proposed early prediction for both miscarriage and threatened miscarriage [3], [14], [15]), mortality (implemented machine learning techniques to forecast in-hospital mortality [16]- [18]),placenta previa, preterm delivery (utilizing machine learning for the early prediction of spontaneous preterm birth [19]- [22]), stillbirth (Data-Driven Stillbirth Prediction in Pregnancy [23]), and Urinary Tract Infection (UTI) exploring machine learning algorithms for predicting UTI [24]- [27]. It is encouraging to see the advancements in this field, which have the potential to improve the health and safety of expectant mothers.…”
Section: IImentioning
confidence: 99%